Case report: Successful treatment of renal-limited thrombotic microangiopathy secondary to chronic lymphocytic leukemia - Nasr, Kristina; Karam, Sabine; Mazepa, Marshall; Czyzyk, Jan; Klomjit, Nattawat (Frontiers in Nephrology, 2024)
Thrombotic microangiopathy (TMA) is a rare renal complication of patients with chronic lymphocytic leukemia (CLL) and is often associated with peripheral features. We present the first case of CLL patients with renal-limited TMA. A 70-year-old female patient with a history of well-controlled type 2 diabetes and baseline albuminuria of 87.2 mg/g 1 year prior and CLL was on active surveillance only. Her baseline white blood cell (WBC) was 202.6 x 103/µl. She presented with nephrotic syndrome with proteinuria of 10 g/g and a subsequent unremarkable serologic work-up. A kidney biopsy revealed diabetic glomerulosclerosis and chronic TMA. Initially, she was treated conservatively with angiotensin receptor blockade and sodium glucose cotransporter-2 inhibition but progressed with increased proteinuria of 17 g/g. Complement functional panel testing was pursued and showed dysregulation of the classical and alternative complement pathways. We decided to treat CLL which was suspected to be the culprit. At 9 months post-ibrutinib initiation, there was a 90% reduction in the WBC as well as a 94% reduction in proteinuria (17 g/g to 0.97 g/g). This case emphasizes the role of complement dysregulation in the pathogenesis of TMA in CLL patients. Treatment of CLL can restore complement dysregulation and improve renal outcomes.